Refined evaluation methods for preventive maintenance of project-level asphalt pavement based on confusion-regression model - Li, Yan; Zou, Zhengbo; Zhang, Jiupeng; He, Yinzhang; Huang, Guojing; Li, Junbo (Construction & building materials, 2023)
•Airport pavement preventive maintenance three-level evaluation index system is established.•PM decisions are considered as the binary classification problem.•The asphalt pavement decay model is developed based on PCI.•Project-level asphalt pavement PM timing was determined through confusion matrix. Accurate evaluation of the performance of airport pavement can help managers make scientific and systematic preventive maintenance (PM) decisions, ensuring pavement safety and extending service life. To this end, firstly, this paper sorted out the pavement performance evaluation index system, based on which a multi-dimensional evaluation system for PM was proposed, including control indexes, macroscopic indexes, and microscopic indexes. Then, the pavement decay model based on the pavement condition index (PCI) was developed, and the regression model between PCI and International roughness index (IRI) and friction coefficient (μ) was established. Finally, by converting the PM decisions for project-level pavement into a binary classification problem in machine learning, the optimal maintenance thresholds and intervals for PM of each index were determined using receiver operating characteristic (ROC) curve and Kolmogorov-Smirnov (K-S) curve. The optimal threshold represents the threshold when the index can separate the binary classification problem (PM decisions) with maximum probability. Based on confusion-regression model, the pavement performance can be evaluated more comprehensively, and the timing of PM can be accurately determined. The model helps airport managers develop accurate PM plans to address future maintenance needs.